National on sample of Syrian citizen The Fact of the Responsibility Study applied on sample of volunteers in the Syrian civil environmental difference in Tartous city - musalam, Adnan; Ibrahim, Bana (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This study is trying to research in fact of the Responsibility National on sample of Syrian citizen in the light of what is happening in confidentiality of the Syrian social reality of the economic and socio-cultural events , requisite of the citizen to translate its direction towards positive or negative direction. So this research on the oration level to monitor the relationship between Responsibility of National and some variables such as :the relationship between the citizen and the subject of his own Responsibility and Citizenship and the degree to satisfy need of the relationship between Responsibility and national culture and societal institutions either to raise a research level, the researcher spotted on relationship with national Responsibility for some variables such as race education professional place of residence-the age of the citizen . The study identified a sample of participants from civil society's activities in the environmental where the sample was (76) and formed with Its diverse models the focus of my intention to discuss researcher . The results showed the there are significant to the Responsibility of national and appreciated everywhere for the Syrian citizen difference in urban and rural avers, age group his social statues for the benefit of high performance among citizen unmarried(single) versus that there is no statistically sign vesicant difference between national Responsibility and educational level of the Syrian citizen. Ther is no difference between national Responsibility and the profession practiced by the Syrian citizen as well the set of the citizen ( male or female) of any Responsibility of the Syrian citizen and Citizenship Syrian alike.